2020
DOI: 10.1039/d0ra00653j
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal quantum dot light-emitting diodes employing solution-processable tin dioxide nanoparticles in an electron transport layer

Abstract: QD-LEDs have gained tremendous attention to potentially replace current emissive display technologies. Here, we explore solution-processable SnO2 nanoparticles (NPs) as alternatives to ZnO for the electron transporting layer in QD-LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We chose SnO 2 NPs for the second electron injection layer because of their excellent solution processability, high transparency in the visible region ( Figure S1), which is similar to ZnO NPs, and decent electron-transport properties as evidenced by the previous employment in perovskite solar cells [28] and organic light-emitting diodes [29]. In addition, in our recent study [20], we have examined the use of SnO 2 NPs for the ETL in QD-LEDs, and found out SnO 2 NPs have favorable interfacial properties with QDs that do not induce spontaneous electron injection; SnO 2 NPs have lower conduction band minimum (CBM) (see Figure 1b) and lower carrier concentration compared to ZnO NPs. In order to take advantage of SnO 2 NPs while maintaining an excellent electron transporting ability of the standard ZnO-based ETL, we propose a new ETL platform comprising the stack of ZnO and SnO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose SnO 2 NPs for the second electron injection layer because of their excellent solution processability, high transparency in the visible region ( Figure S1), which is similar to ZnO NPs, and decent electron-transport properties as evidenced by the previous employment in perovskite solar cells [28] and organic light-emitting diodes [29]. In addition, in our recent study [20], we have examined the use of SnO 2 NPs for the ETL in QD-LEDs, and found out SnO 2 NPs have favorable interfacial properties with QDs that do not induce spontaneous electron injection; SnO 2 NPs have lower conduction band minimum (CBM) (see Figure 1b) and lower carrier concentration compared to ZnO NPs. In order to take advantage of SnO 2 NPs while maintaining an excellent electron transporting ability of the standard ZnO-based ETL, we propose a new ETL platform comprising the stack of ZnO and SnO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of QD-based light-emitting diodes (QD-LEDs) has been improved steadily over the past two decades, and one of the most important breakthroughs was made by employing a metal oxide semiconductor in the electron transport layer (ETL). Suitable energy levels and high electron mobility of metal oxide semiconductors led to efficient charge injection and transport, thereby resulting in notable progress in the luminescence efficiency of QD-LEDs [17][18][19][20]. Various types of metal oxide semiconductors have been employed and investigated, and among those metal oxide semiconductors, 2 of 9 zinc oxide (ZnO) has been the most widely employed because of their easy processability, excellent electrical properties, and transparency [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors affecting their performance include a high electron mobility, an amorphous morphology, a high glass transition temperature, and the ability to be deposited as a uniform thin film. Some of the commonly used polymers and metal oxides for ETL are PBD, PBD-PMMA, BND, ZnO, SnO 2 , and TiO 2 [69][70][71].…”
Section: Enhancing Electron Mobility: Electron Transport and Injection Layersmentioning
confidence: 99%
“…II-VI semiconducting nanomaterials have attracted a lot of attention owing to their potential applications in light emitting diodes [1][2][3], solar cells [4] and optical devices [5]. Cadmium sulfide (CdS) is one of the most studied semiconductors with a direct band gap of 2.42 eV.…”
Section: Introductionmentioning
confidence: 99%